Sustaining Islamic Preaching Through Digital Media: The Case of PCIM Turkey During the Covid-19 Pandemic - Hermawan, Ahmad; Kharis Nugroho (Universitas Muhammadiyah Yogyakarta, 2026)
The COVID-19 pandemic has reshaped multiple aspects of social and religious life, including the practice of Islamic da'wah. Restrictions on physical gatherings and the temporary closure of public religious spaces rendered conventional preaching activities—such as mosque-based sermons, village outreach, and intercity da'wah travel—largely impracticable. In response to these constraints, Islamic preachers increasingly adopted digital platforms, including Zoom, Microsoft Teams, and YouTube, to sustain religious communication. This study employs a content analysis approach to examine online mass-media materials produced by PCIM Turkey (Pimpinan Cabang Istimewa Muhammadiyah Turki) during the COVID-19 pandemic, focusing on virtual da'wah efforts. The research aims to identify the forms and extent of transformation in da'wah practices implemented by PCIM Turkey as an adaptive response to pandemic-related limitations. Guided by a sociological transformation framework, the findings demonstrate that PCIM Turkey successfully shifted from conventional face-to-face preaching to fully virtual modes of da'wah. This transition enabled the continuity, accessibility, and sustainability of da'wah activities throughout the pandemic period.